Synthesis of magnetically separable Fe3O4–Au–CdS kinked heterotrimers incorporating plasmonic and semiconducting functionalities - Javaid, S.; Li, X.; Wang, F.; Chen, W.; Pang, Ying Ping; Wang, Shaobin; Jia, Guohua; Jones, Franca (ROYAL SOC CHEMISTRY, 2019)
This journal is © The Royal Society of Chemistry. Dimension, composition and configuration are the primary aspects of semiconductor based hybrid heterostructures that govern their properties. To achieve desired functionalities within a single nanoparticle system, numerous synthetic approaches are available which may be suitable for achieving the target combination but these can be complex and tedious. In this work, a simple seeded-growth approach was employed to obtain an iron oxide-gold-cadmium sulfide (Fe3O4-Au-CdS) heterotrimer with a unique morphology manifesting magnetic, plasmonic and semiconducting properties. In a straightforward two-step synthesis process, Au-Fe3O4 dimer was injected as a seed into the Cd precursor solution for the growth of one-dimensional (1D) kinked CdS-5 nanorods on it. The synthesized Fe3O4-Au-CdS heterotrimer was tested in photocatalytic water-reduction reaction, revealing its potential as a photocatalyst for the hydrogen evolution reaction (HER), where each domain within the heterotrimer played a distinct role including light absorption, charge separation and magnetic separation. A post-synthetic modification on the semiconductor part was also performed where kinked CdS nanorod was cation exchanged with Ag2S leading to the formation of another heterotrimer of Fe3O4-Au-Ag2S while retaining the same morphology and expanding the palette of heterotrimers.